Pengaruh Gaya Kepemimpinan Transformasional dan Stres Kerja terhadap Kinerja Pegawai dengan Dimediasi oleh Kepuasan Kerja (studi pada KPPN Makassar 1 dan KPPN Makassar 2) - Akbar, Royhul; Noermijati, Noermijati; Troena, Eka Afnan (Universitas Brawijaya, Indonesia, 2016)
This study aimed to analyze the effect of transformational leadership style to employee performance, the effect of job stress to employee performance, job satisfaction as mediator on tranformational leadership style, and the effect of job stress to employee performance. The population in this study is all of employees with the rank of executive (nonofficial) at the State Treasury Service (KPPN) Makassar 1 and 2 amounted 61 people.The sampling technique using census method, the number of samples that can be used in this study is 57 people. Analysis model used in this study is descriptive analysis, and path analysis using SmartPLS software version 2.0. The results showed that there are a positive and significant effect of transformational leadership style to employee performance, negative and significant effectof job stress to employee performance, job satisfaction mediated the effect of job stress to employee performance, and job satisfaction did not mediate the effect of transformational leadership style to employee performance.